THE IMPORTANCE OF RESEARCH METHODS IN TRANSLATION THEORY - Sheraliyeva, Shaxnoza (Журнал иностранных языков и лингвистики, 2023)
Our article analyzes different methodological approaches emerging from theoretical articles published in translation studies journals. To reflect the diversity of perspectives, a series of small articles in three journals included in both the Thomson and Reuters Social Sciences Information Index and the Arts and Humanities Information Index were reviewed. The article discusses what level of accuracy the methods used can achieve through formalization. It begins by defining translation theory before outlining the main body of articles to be examined. Next, four methods are described and discussed to provide recommendations for further research on translation theory.